Molybdenum-doped iron oxide nanostructures synthesized via a chemical co-precipitation route for efficient dye degradation and antimicrobial performance: in silico molecular docking studies. Issue 54 (9th December 2022) - Shujah, Tahira; Shahzadi, Anum; Haider, Ali; Mustajab, Muhammad; Haider, Afsah Mobeen; Ul-Hamid, Anwar; Haider, Junaid; Nabgan, Walid; Ikram, Muhammad
Abstract : In this research, various concentrations of molybdenum (2, 4 and 6 wt%) doped Fe3 O4 nanostructures (Mo-Fe3 O4 NSs) were prepared via a co-precipitation technique. Abstract : In this research, various concentrations of molybdenum (2, 4 and 6 wt%) doped Fe3 O4 nanostructures (Mo-Fe3 O4 NSs) were prepared via a co-precipitation technique. Various techniques were then used to investigate the optical, morphological and structural properties of the NSs in the presence of the dopant materials. X-ray diffraction (XRD) was used to investigate the crystalline nature of the prepared NSs and confirm the orthorhombic and tetragonal structure of Fe3 O4, with a decrease in crystallinity and crystallite sizes of 36.11, 38.45, 25.74 and 24.38 nm with increasing concentration of Mo (2, 4 and 6%). Fourier-transform infrared (FTIR) spectroscopy analysis was carried out to examine the functional groups in the NSs. Structure, surface morphology and topography were examined via field emission scanning electron microscopy (FE-SEM) and transmission electron microscopy (TEM), which confirmed the fabrication of nanoparticles and nanorods and a floccule-like morphology with a higher doping concentration and the interlayer d -spacing was calculated using high-resolution (HR)TEM, the results of which were a good match to the XRD data. The presence of Mo, Fe and O in a lattice of Mo (2, 4 and 6%) doped Fe3 O4 was confirmed by energy dispersive X-ray spectroscopy (EDS) analysis. The energy band gap ( E g ) was measured via the optical analysis of pure and doped samples, showing a decrease from 2.76 to 2.64 eV. The photoluminescence (PL) spectra exhibit a higher charge combination rate of electron–hole pairs with a higher concentration of doping. The NSs exhibited excellent catalytic activity (CA) in degrading methylene blue (MB) dye in a basic medium by around 86.25%. Additionally, the antimicrobial activity was tested against Escherichia coli ( E. coli ) bacteria. Pairs of electrons and holes are the fundamental basis for generating reactive oxygen species that kill bacteria. The significant inhibition zones were calculated against E. coli bacteria at around 3.45 mm compared to ciprofloxacin. In silico docking investigations of the Mo-Fe3 O4 NSs for dihydropteroate synthase (DHPS, binding score: 6.16 kcal mol −1 ), dihydrofolate reductase (DHFR, binding score: 6.01 kcal mol −1 ), and β-ketoacyl-acyl carrier protein synthase III (FabH, binding score: 5.75 kcal mol −1 ) of E. coli show the suppression of the aforementioned enzymes as a potential mechanism besides their microbicidal assay.